Micronutritional supplementation with a holoBLG‐based FSMP (food for special medical purposes)‐lozenge alleviates allergic symptoms in BALB/c mice: Imitating the protective farm effect. Issue 3 (3rd December 2021) - Afify, Sheriene Moussa; Regner, Andreas; Pacios, Luis F.; Blokhuis, Bart R.; Jensen, Sebastian A.; Redegeld, Frank A.; Pali‐Schöll, Isabella; Hufnagl, Karin; Bianchini, Rodolfo; Guethoff, Sonja; Kramer, Matthias F.; Fiocchi, Alessandro; et al.
Abstract: Background: Previously, the protective farm effect was imitated using the whey protein beta‐lactoglobulin (BLG) that is spiked with iron‐flavonoid complexes. Here, we formulated for clinical translation a lozenge as food for special medical purposes (FSMP) using catechin‐iron complexes as ligands for BLG. The lozenge was tested in vitro and in a therapeutical BALB/c mice model. Methods: Binding of iron‐catechin into BLG was confirmed by spectroscopy and docking calculations. Serum IgE binding of children allergic or tolerating milk was assessed to loaded (holo‐) versus empty (apo‐) BLG and for human mast cell degranulation. BLG and Bet v 1 double‐sensitized mice were orally treated with the holoBLG or placebo lozenge, and immunologically analysed after systemic allergen challenge. Human PBMCs of pollen allergic subjects were flow cytometrically assessed after stimulation with apoBLG or holoBLG using catechin‐iron complexes as ligands. Results: One major IgE and T cell epitope were masked by catechin‐iron complexes, which impaired IgE binding of milk‐allergic children and degranulation of mast cells. In mice, only supplementation with the holoBLG lozenge reduced clinical reactivity to BLG and Bet v 1, promoted Tregs, and suppressed antigen presentation. In allergic subjects, stimulation of PBMCs with holoBLG led to a significant increase of intracellular iron in circulating CD14+ cells with significantly lower expression of HLADR and CD86 compared to their stimulation with apoBLG. Conclusion: The FSMP lozenge targeted antigen presenting cells and dampened immune activation in human immune cells and allergic mice in an antigen‐non‐specific manner, thereby conferring immune resilience against allergic symptoms. Abstract : The whey protein beta‐lactoglobulin BLG binding to micronutrients such as iron‐catechin complexes (holoBLG) was recognized less by IgE antibodies of children allergic to milk, leading to reduced mast cell degranulation. BLG also facilitated catechin‐dependent activation of the anti‐inflammatory arylhydrocarbon receptor. In mice, oral application of a holoBLG‐based lozenge which also contained zinc and vitamin A, improved the allergic symptoms of double‐sensitized mice independent of the allergens they were challenged with. Double‐sensitized mice supplemented with the holoBLG lozenge also had reduced levels of allergen‐specific antibodies and a lower frequency of activated antigen presenting cells.